Tip Enhanced Raman Spectroscopy of Rhodamine 6G on nanostructured gold substrate. (January 2016) - Moretti, Manola; Das, Gobind; Torre, Bruno; Allione, Marco; Di Fabrizio, Enzo
Abstract: A new concept based setup for Tip Enhanced Raman Scattering measurement assisted by gold nanostructure is presented, that can provide a platform for gap-mode enhancement of the signal at the single molecule level conjugated with controlled spatial localization of the molecule under investigation and a method to determine the diffraction limit properties of the tip. In essence, this effect is obtained illuminating a gold coated AFM tip which is raster scanned over a nanostructured gold substrate, after chemisorption of a Raman active molecule. We expect that the near-field Raman enhancement would be given by the gap-mode effect of the two facing nano-features. Thanks to the nanostructured substrate, we verify that the resolution of the Raman mapping signal is well below the diffraction limit given by the combination of the optics geometry and the laser wavelength. We show that the gap-mode TERS can generate an estimated field- enhancement ( g ) of 20 in localized areas of the sample and we demonstrate the ability to spatially define the molecule position (by Raman mapping) at the tens of nanometers scale. Highlights: Gap-mode TERS of Rhodamine 6G in upright configuration was performed. A nanofabricated gold substrate was used to estimate the tip integrity. Both TERS confinement and enhancement of Raman signal were proven.